Implementasi Barcode untuk Sistem Informasi Absensi pada PT. Coca Cola Distribution Indonesia Pekanbaru - Nurmaliana Pohan (RJOCS (Riau Journal of Computer Science), 2016)
Attendance generally require proof of presence in the form of signatures each employee. Every employee at PT. Coca Cola Distribution Indonesia Pekanbaru must confirm their attendance every entrance or exit from the company. Attendance that is used today is doing a signature on the security station. So there is the possibility of cheating. Sometimes employees are not in the corporate environment but absences already signed. Attendance recapitulated every 25th. Then absences were sent to Padang to work more competent in processing employees. After the author studied the attendance system that exists today in the PT. Coca Cola Distribution Indonesia Pekanbaru. Then the author makes an attendance that use information systems and databases for data storage and employee attendance reports willbe viewable on a larger office in charge of processing the employees. Attendance is made to apply existing barcode technology on every ID Card employee to minimize of fraud.